Pathogenic Mitochondrial tRNA Point Mutations: Nine Novel Mutations Affirm Their Importance as a Cause of Mitochondrial Disease. Issue 9 (14th August 2013) - Blakely, Emma L.; Yarham, John W.; Alston, Charlotte L.; Craig, Kate; Poulton, Joanna; Brierley, Charlotte; Park, Soo‐Mi; Dean, Andrew; Xuereb, John H.; Anderson, Kirstie N.; Compston, Alistair; Allen, Chris; et al.
<x xml:space="preserve">Abstract</x> We describe novel mitochondrial tRNA point mutations in nine families associated with a diverse range of clinical presentations, providing functional evidence to classify six of these variants as definitely pathogenic, with the remaining three classed as possibly pathogenic. Our report adds to the large number of mitochondrial tRNA variants associated with disease and confirms mitochondrial tRNA mutations as an important subgroup of human genetic disorders. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>